G1 cyclins link proliferation, pluripotency and differentiation of embryonic stem cells - Liu, Lijun; Michowski, Wojciech; Inuzuka, Hiroyuki; Shimizu, Kouhei; Nihira, Naoe Taira; Chick, Joel M.; Li, Na; Geng, Yan; Meng, Alice Y.; Ordureau, Alban; Kołodziejczyk, Aleksandra; Ligon, Keith L.; et al. (Nature cell biology, 2017)
Progression of mammalian cells through the G1 and S phases of the cell cycle is driven by the D-type and E-type cyclins. According to the current models, at least one of these cyclin families must be present to allow cell proliferation. Here, we show that several cell types can proliferate in the absence of all G1 cyclins. However, following ablation of G1 cyclins, embryonic stem (ES) cells attenuated their pluripotent characteristics, with the majority of cells acquiring the trophectodermal cell fate. We established that G1 cyclins, together with their associated cyclin-dependent kinases (CDKs), phosphorylate and stabilize the core pluripotency factors Nanog, Sox2 and Oct4. Treatment of murine ES cells, patient-derived glioblastoma tumour-initiating cells, or triple-negative breast cancer cells with a CDK inhibitor strongly decreased Sox2 and Oct4 levels. Our findings suggest that CDK inhibition might represent an attractive therapeutic strategy by targeting glioblastoma tumour-initiating cells, which depend on Sox2 to maintain their tumorigenic potential. Liu et al. show that G1 cyclins and their cyclin-dependent kinases regulate the pluripotent state by driving phosphorylation of Nanog, Oct4 and Sox2, thereby identifying a direct connection between G1 cyclins and pluripotency factors.